2017
DOI: 10.1080/09687599.2017.1320271
|View full text |Cite
|
Sign up to set email alerts
|

Forced marriage of people with learning disabilities: a human rights issue

Abstract: This paper reports some of the findings of an exploratory study which sought to better understand the demographics of forced marriage of people with learning disabilities and the contexts in which such marriages may occur. It was found that forced marriages of people with and without learning disabilities showed broad similarities in relation to ethnicity, some differences in terms of age and substantial differences in terms of gender. Men and women with learning disabilities are equally likely to be victims o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…For example, Smelzer [41] documents that while disabled women face the same uncertainties around pregnancy as all women, they are also subject to unique harrowing experiences, such as receiving unsolicited advice for termination from healthcare professionals. Lastly, women and girls with disabilities are vulnerable to forms of abuse, such as forced marriage [42] and sexual abuse [43,44], and people with disabilities are generally from sexual education, which can obstruct the recognition of abuse as well as the seeking of support (e.g., reporting abuse to the authorities). Understanding how issues like abuse affect people with disabilities, and particular categories of disabled people like women, or adolescent girls, is key to designing effective prevention strategies to engender autonomy and reduce risk of harm.…”
Section: What Disaggregating Data Tells Usmentioning
confidence: 99%
“…For example, Smelzer [41] documents that while disabled women face the same uncertainties around pregnancy as all women, they are also subject to unique harrowing experiences, such as receiving unsolicited advice for termination from healthcare professionals. Lastly, women and girls with disabilities are vulnerable to forms of abuse, such as forced marriage [42] and sexual abuse [43,44], and people with disabilities are generally from sexual education, which can obstruct the recognition of abuse as well as the seeking of support (e.g., reporting abuse to the authorities). Understanding how issues like abuse affect people with disabilities, and particular categories of disabled people like women, or adolescent girls, is key to designing effective prevention strategies to engender autonomy and reduce risk of harm.…”
Section: What Disaggregating Data Tells Usmentioning
confidence: 99%
“…Whilst many of the factors which precipitate such marriages are benign, they may nevertheless lead to outcomes which harm people with intellectual disabilities. As has been noted elsewhere (Clawson, & Fyson, 2017) people with intellectual disabilities have the same universal human rights as other people and in the UK this includes the protection of the law against forced marriage. In order for these rights to be made a reality, a more widespread understanding of the risk of forced marriage, including the reasons why carers may opt for forced marriage, is needed.…”
Section: Con Clus Ionmentioning
confidence: 78%
“…As noted in the introduction, previous studies have reported professionals to believe that some parents “force” their adult child with intellectual disabilities to marry in order to secure a long‐term carer (Clawson, & Fyson, 2017; Patterson et al, 2018; Rauf et al., 2013). In this context, both community acceptance and support for individuals with intellectual disability and the availability or otherwise of public services are important areas of consideration, because they affect whether parents feel the need to consider marriage as a means of securing long‐term care.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations